'The very worst things': violence and vulnerability in Djamila Sahraoui's Yema (2012). Issue 3 (3rd July 2019) - Flood, Maria
ABSTRACT: This article explores the connections between vulnerability, gender and terrorist violence in relation to Algerian filmmaker Djamila Sahraoui's Yema (2012). The film is situated in relation to Sahraoui's oeuvre, and within wider debates around the changing nature of political violence and its representation in Maghrebi and Hollywood cinema. This comparison underlines Yema 's innovatory formal and thematic focus on slow narrative time, sparse aesthetics and fragile, intimate images. The article then examines the concept of vulnerability in relation to terrorism, in particular linking Sahraoui's choice of formal techniques to the film's thematic staging of various modes of physical and psychical vulnerability. The allegorical and mythological motifs used in Yema are considered in relation to the gendering of the figures of victim and agent in the film. Through a feminist reconfiguration of the myth of Medea, the article suggests that in the film's dramatisation of a mother who inflicts suffering, larger questions are raised about personal and political responses to the feelings of exposure that terrorist violence engenders.